2016
DOI: 10.3390/data1020010
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Stations for Calibration/Validation of Thermal Sensors over Spain

Abstract: Abstract:The Global Change Unit (GCU) at the University of Valencia has been involved in several calibration/validation (cal/val) activities carried out in dedicated field campaigns organized by ESA and other organisms. However, permanent stations are required in order to ensure a long-term and continuous calibration of on-orbit sensors. In the framework of the CEOS-Spain project, the GCU has managed the set-up and launch of experimental sites in Spain for the calibration of thermal infrared sensors and the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Therefore, there is no universal method that always provides accurate LSTs from all satellite TIR data, and it is not easy to say which algorithm is superior to others [7]. The accuracy of the radiometric measurements and emissivity is the primary uncertainty for ground-based LST retrievals [119][120][121][122][123]. Sobrino and Skoković [119,122] presented an example of an error budget for The Global Change Unit (GCU) sites at the University of Valencia, and Table 8 indicates the impact of the parameter uncertainty ranges on ground-based LST.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there is no universal method that always provides accurate LSTs from all satellite TIR data, and it is not easy to say which algorithm is superior to others [7]. The accuracy of the radiometric measurements and emissivity is the primary uncertainty for ground-based LST retrievals [119][120][121][122][123]. Sobrino and Skoković [119,122] presented an example of an error budget for The Global Change Unit (GCU) sites at the University of Valencia, and Table 8 indicates the impact of the parameter uncertainty ranges on ground-based LST.…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of the radiometric measurements and emissivity is the primary uncertainty for ground-based LST retrievals [119][120][121][122][123]. Sobrino and Skoković [119,122] presented an example of an error budget for The Global Change Unit (GCU) sites at the University of Valencia, and Table 8 indicates the impact of the parameter uncertainty ranges on ground-based LST. It is interesting to discuss our results in comparison with those of other studies that utilized SURFRAD LST measurements and Landsat data for LST retrieval.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While surface reflection of downwelling longwave radiation is ignored, Sun et al [32] discussed the effects of these two factors and found that the total effect may be a slight underestimation of the skin temperature. Generally, estimated impact of uncertainty in relevant parameters on in situ LST are as follows: radiometric calibration uncertainty of ±0.2 to 0.5 K can impact LST as much as 0.2 K; emissivity uncertainty of ±1% can impact LST by as much as 0.3 K; downwelling atmospheric radiance uncertainty of ±10% can impact LST by as much as 0.1 K [47].…”
Section: Mod11mentioning
confidence: 99%
“…The thermal products were obtained directly from the NASA, then they were georeferenced and multiplied by the MOD11 scaling factor of 0.02. Depending on the angle of image acquisition, the error was between 1.5-2 • C, as [48,49] described it.…”
Section: Remote-sensing Datamentioning
confidence: 99%